Composite alkaline ionic membrane as well as preparation method and application thereof
By combining the quaternized anion exchange membrane polymer with the ionic solvated polymer nanofiber membrane, a composite alkaline ion membrane is constructed, which solves the problem of insufficient conductivity and mechanical properties of the anion exchange membrane and achieves efficient hydrogen Oxygen conduction and mechanical strength increase, suitable for alkaline electrolysis and hydrogen production.
Patent Information
- Application Number
- CN202411428141.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-14
AI Technical Summary
In the existing alkaline water electrolytic cells, the anion exchange membrane has a low ion conductivity and insufficient mechanical performance, resulting in poor voltage efficiency and safety hazards. The introduced reinforcement often damages the mechanical properties, making it difficult to ionic conductivity and mechanical properties. Make trade-offs between them.
The composite alkaline ion membrane composed of quaternized anion exchange membrane polymer and ionic solvated polymer nanofiber membrane is used to construct a synergistic conduction mechanism and chemical cross-linking of hydroxide to enhance ionic conductivity through covalent bonding. rate and mechanical strength.
The ionic conductivity and mechanical strength of the composite alkaline ion film are significantly improved, the problems of insufficient conductivity and mechanical properties of the anion exchange film are solved, and the efficiency and safety of the electrolytic cell are provided.
Smart Images

Figure CN119307096A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite alkaline ion membrane and a preparation method and application thereof, belonging to the technical field of alkaline ion membranes. Background Art
[0002] In today's world, energy shortage and environmental pollution problems are becoming increasingly prominent, forcing people to accelerate the pace of exploring new energy sources. Energy-saving and cost-effective water electrolysis is essential for the large-scale implementation of renewable energy. Proton exchange membrane water electrolyzers are limited in their widespread application due to the use of expensive perfluorosulfonic acid membranes and precious metal catalysts. Alkaline environments allow water electrolyzers to completely avoid the use of precious metal catalysts, which has promoted their rapid development in recent years. As a key material for alkaline water electrolyzers, alkaline membranes are currently divided into three categories: traditional porous diaphragms, anion exchange membranes, and ion solvation membranes. Traditional porous diaphragms are usually composed of stable inert polymers and hydrophilic inorganic fillers (to enhance mechanical properties) and have a porous structure, which transports hydroxide ions through high-concentration alkali solutions stored in the pore structure. However, the traditional alkaline water electrolyzer based on porous membranes has a large internal resistance of the electrolyzer due to its thick porous diaphragm, resulting in poor voltage efficiency. At the same time, the generated hydrogen and oxygen gases are also easy to permeate bidirectionally through the porous diaphragm, making the hydrogen production rate very low and posing safety hazards. Therefore, dense anion exchange membranes and ion solvation membranes have received increasing attention. Anion exchange membranes are usually polymers with fixed cationic side groups, and hydroxide ions coordinate with the cationic side groups, thereby dissociating and hopping in water. However, anion exchange membranes are still limited by low ion conductivity and insufficient mechanical properties.
[0003] At present, the common means to improve the ion conductivity of anion exchange membrane is to increase its ion exchange capacity, but too high ion exchange capacity often brings too high water absorption and swelling problems, which will damage the mechanical properties of the membrane. In order to improve the mechanical properties, researchers introduce the support skeleton into the anion exchange membrane. For example, Chinese patent CN113249980A mixes polyvinylbenzyl chloride, dimethylamino-N-ethyl-N, N-dimethylhexan-1-amine and dispersant and applies them on polytetrafluoroethylene-based membrane for hot pressing film formation, and then obtains a fiber-reinforced anion exchange membrane by ion exchange. However, since the patent uses an inert reinforcement polytetrafluoroethylene that cannot conduct hydroxide, its ion conductivity is reduced. Therefore, the introduction of an ion transport function reinforcement is of great significance for solving the problem of balancing the ion conductivity and mechanical properties of anion exchange membrane. In addition, it is also crucial to optimize and further improve its ion conductivity by designing the synergistic effect between the anion exchange membrane and the reinforcement with ion transport function.
[0004] Therefore, it is of great significance to study a composite alkaline ion membrane and its preparation method and application to solve the problems existing in the prior art. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a composite alkaline ion membrane and a preparation method and application thereof.
[0006] In order to achieve the above object, the scheme adopted by the present invention is as follows:
[0007] A composite alkaline ion membrane is obtained by anion exchange through a composite membrane composed of a quaternized anion exchange membrane polymer and an ion solvated polymer nanofiber membrane;
[0008] The quaternized anion exchange membrane polymer is distributed on the surface (preferably on both sides of the surface, but only on one side of the surface is also within the protection scope of the present invention) and pores of the ion solvated polymer nanofiber membrane, and the two are bound by covalent bonds.
[0009] As the preferred technical solution:
[0010] A composite alkaline ion membrane as described above, wherein the anion exchange membrane type polymer is prepared by halogen modification of polymer A, polymer A is one or more of polyphenylene ether, polyarylene ether sulfone (PAES), polyarylene ether ketone, polyethylene, polystyrene, polynorbornene, polytetrafluoroethylene, poly(styrene-b-(ethylene-co-butylene)-b-styrene) (SEBS) and polysulfone (PSU), and the halogen modification method is one or more of chloromethylation and bromohexylation.
[0011] As described above, the composite alkaline ion membrane, the ion solvated polymer nanofiber membrane is prepared by electrospinning of an ion solvated polymer, and the ion solvated polymer is one or more of poly[2,2'-(meta-phenyl)-5,5'-bibenzimidazole] (mPBI), poly(2,5-benzimidazole) (ABPBI) and poly(4,4'-diphenyl ether-5,5'-bibenzimidazole) (OPBI).
[0012] In the composite alkaline ion membrane as described above, the mass fraction of the quaternized anion exchange membrane type polymer in the composite membrane is 60-90%.
[0013] The composite alkaline ion membrane as described above has a thickness of 40 to 50 μm, a tensile strength of 20 to 50 MPa, a swelling rate of 8 to 14% at 80° C., and an ionic conductivity of 50 to 120 mS / cm at 80° C.
[0014] In the composite alkaline ion membrane as described above, the thickness of the ion-solvated polymer nanofiber membrane is 30-40 μm, the pore size is 0.8-7 μm, the porosity is 70-90%; and the diameter of the ion-solvated polymer nanofiber is 400-2000 nm.
[0015] The present invention also provides a method for preparing a composite alkaline ion membrane as described in any of the above items, wherein an anion exchange membrane type polymer solution is coated on the surface of an ion-solvated polymer nanofiber membrane and filled into the pores on the membrane, and then a cross-linking reaction, a quaternization reaction and anion exchange reaction are sequentially performed to obtain a composite alkaline ion membrane.
[0016] As the preferred technical solution:
[0017] The preparation method of the composite alkaline ion membrane as described above, the specific preparation steps are as follows:
[0018] (1) Mixing polymer A, catalyst B, and modifying agent C in solvent D in an ice water bath, reacting at room temperature, and after the reaction is completed, precipitating the product in solvent E, and drying to obtain an anion exchange membrane polymer;
[0019] (2) dissolving the anion exchange membrane type polymer obtained in step (1) in solvent F, and stirring at room temperature to completely dissolve the anion exchange membrane type polymer solution;
[0020] (3) dissolving the ionic solvated polymer in solvent G to prepare a spinning solution, heating and stirring until completely dissolved, then electrospinning, and then drying to obtain an ionic solvated polymer nanofiber membrane;
[0021] (4) coating the anion exchange membrane type polymer solution obtained in step (2) on the surface of the ion solvated polymer nanofiber membrane prepared in step (3) and filling the pores on the membrane;
[0022] (5) cross-linking the ion-solvated polymer nanofiber membrane coated with the anion exchange membrane type polymer solution in step (4), so that the anion exchange membrane type polymer and the ion-solvated polymer nanofiber membrane undergo a cross-linking reaction to covalently bond to obtain a cross-linked membrane;
[0023] (6) soaking the cross-linked membrane obtained in step (5) in a trimethylamine solution for quaternization reaction, and converting the halogen groups in the anion exchange membrane type polymer into quaternary ammonium salt functional groups through the reaction between trimethylamine and the anion exchange membrane type polymer in the cross-linked membrane, thereby obtaining a quaternary ammonium cross-linked membrane, i.e., a composite membrane;
[0024] (7) Immersing the composite membrane obtained in step (6) in a sodium hydroxide solution or a potassium hydroxide solution to carry out anion exchange reaction, converting anions in the composite membrane into hydroxides, thereby obtaining a composite alkaline ion membrane.
[0025] The method for preparing a composite alkaline ion membrane as described above, in step (1), the catalyst B is one or more of anhydrous tin tetrachloride, aluminum chloride, zinc chloride and concentrated hydrochloric acid (concentration of 37wt%), the modification reagent C is one or more of 1,4-dichloromethoxybutane (BCMB), chloromethyl ether, paraformaldehyde and 6-bromohexanoyl chloride (paraformaldehyde and 6-bromohexanoyl chloride must be used together as the modification reagent), the solvent D is one or more of chloroform and p-xylene, and the solvent E is one or more of methanol, ethanol and propanol; the ratio of the amount of polymer A, catalyst B, modification reagent C, solvent D and solvent E is 1-5g:1-4mL:5-20mL:40-80mL:200-500mL; the reaction time at room temperature is 3-7h, the drying temperature is 30-80°C, and the drying time is 24-48h;
[0026] In step (2), the solvent F is a mixture of chloroform and p-xylene, the mass ratio of chloroform to p-xylene is 2:1; the concentration of the anion exchange membrane polymer solution is 8 to 12 wt %; the time of stirring and dissolving at room temperature is 10 to 30 h;
[0027] In step (3), the solvent G is one or more of N,N-dimethylacetamide, N,N-dimethylformamide and dimethyl sulfoxide; the concentration of the ionic solvated polymer in the spinning solution is 10-20wt%; the electrospinning process parameters are: temperature 25-35°C, humidity 25-35%, voltage 18-24kV, push speed 0.1-0.5mL / h, receiving distance 12-16cm; drying temperature is 60-80°C, and drying time is 6-18h;
[0028] In step (5), the cross-linking reaction temperature is 60 to 120° C. and the time is 6 to 18 hours;
[0029] In step (6), the concentration of the trimethylamine solution is 30wt%, and the quaternization reaction time is 48h;
[0030] In step (7), the concentration of the sodium hydroxide solution or the potassium hydroxide solution is 1 to 6 M, and the soaking time is 24 to 100 hours.
[0031] The present invention also provides an application of a composite alkaline ion membrane as described in any one of the above items, used as an alkaline ion membrane in alkaline water electrolysis to produce hydrogen, alkaline fuel cells, carbon dioxide conversion or electrochemical synthesis of ammonia.
[0032] The mechanism of the present invention is as follows:
[0033] The general mechanical reinforcement method of anion exchange membrane is to add an inert reinforcement that cannot conduct hydroxide, such as polytetrafluoroethylene, ultra-high molecular weight polyethylene, etc. The consequence of adding an inert reinforcement is inevitably the loss of ion conductivity, that is, a trade-off is made between mechanical strength and ion conductivity. Different from the general reinforcement method, the composite alkaline ion membrane prepared by the present invention has both high ion conductivity and high mechanical strength.
[0034] For the improvement of ionic conductivity, the composite alkaline ion membrane of the present invention constructs a unique hydroxide ion conduction mechanism, which is as follows: in the anion exchange membrane part of the composite alkaline ion membrane, hydroxide is mainly conducted by the cationic group (quaternary ammonium cation) grafted on the main chain of the anion exchange membrane, and the hopping transmission of hydroxide is achieved by the mutual adsorption and dissociation of the cationic group and the hydroxide. The ion-solvated polymer nanofiber membrane in the composite alkaline ion membrane can conduct hydroxide by swelling in alkali solution to form a ternary system of polymer / alkali / water. At the same time, the ion-solvated polymer nanofiber membrane in the composite alkaline ion membrane and the anion exchange membrane-type polymer form a two-phase micro-region through chemical cross-linking, so that the cationic group in the anion exchange membrane and the alkali solution in which the ion-solvated nanofiber membrane is swollen are uniformly mixed at the molecular scale, thereby constructing a fast channel for the coordinated conduction of hydroxide through the cationic group and the alkali solution, thereby improving the ionic conductivity.
[0035] The improvement of mechanical strength and dimensional stability of the composite anion exchange membrane of the present invention comes from two aspects: on the one hand, the introduced ion solvated polymer nanofibers themselves have high mechanical strength, and the nanofibers are prepared into fiber form and added to the composite system to utilize the toughness and high strength of the fiber to strengthen the composite membrane, and at the same time utilize the anti-swelling property of the fiber to improve the dimensional stability of the composite membrane, so that it can better resist physical deformation and damage in the actual working environment of the electrolytic cell. On the other hand, the anion exchange membrane type polymer can undergo a cross-linking reaction with the ion solvated polymer to produce a strong chemical bond, and the strong chemical bond such as covalent bonding can significantly improve the interface and compatibility of the two polymers, thereby improving the physical stability of the composite anion exchange membrane.
[0036] Beneficial effects:
[0037] (1) The composite alkaline ion membrane of the present invention adopts an ion-solvated polymer nanofiber membrane which can itself conduct hydroxide. The two-phase micro-region formed by chemical cross-linking between the nanofiber membrane and the anion exchange membrane polymer can also construct a fast channel for the coordinated conduction of hydroxide through cationic groups and alkaline solution, thereby significantly improving the ionic conductivity of the composite anion exchange membrane.
[0038] (2) The composite alkaline ion membrane of the present invention uses an ion-solvated polymer nanofiber membrane with high mechanical strength as a reinforcing phase. At the same time, the strong chemical bonding between the nanofiber membrane and the anion exchange membrane-type polymer significantly improves the interface and compatibility of the two polymers, further enhancing the mechanical strength and anti-swelling properties of the composite anion exchange membrane.
[0039] (3) The preparation method of the composite alkaline ion membrane of the present invention has a simple preparation process, multiple polymer selectivities, and high economic benefits;
[0040] (4) The composite alkaline ion membrane of the present invention can be applied to the fields of alkaline water electrolysis to produce hydrogen, alkaline fuel cells, carbon dioxide conversion, electrochemical synthesis of ammonia, etc., and has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a surface scanning electron micrograph of the ion-solvated polymer nanofiber membrane in Example 1;
[0042] Figure 2 is a surface scanning electron microscope image of the composite alkaline ion membrane in Example 1;
[0043] Figure 3 This is a scanning electron microscope image of the cross section of the composite alkaline ion membrane in Example 1. DETAILED DESCRIPTION
[0044] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0045] The test methods involved in the performance indicators in the embodiments and comparative examples of the present invention are as follows:
[0046] Tensile strength and elongation at break: The film to be tested is washed or dried according to the test requirements, and then cut into samples with a size of 1×3 cm. The AGS-500ND general material testing machine of Japan Torii Corporation is used to test the breaking strength and elongation of the samples, and the tensile rate is 20 mm / min.
[0047] Ionic conductivity: The membrane samples were cut into samples of 1×4 cm in size and washed with deionized water after ion exchange. The impedance of the membrane was tested at different temperatures using a Solartron electrochemical workstation using a four-electrode method. The test frequency was 0.1 Hz to 100,000 Hz. The ionic conductivity was then calculated using the formula:
[0048]
[0049] Where σ is the ionic conductivity, in S / cm; L is the distance between two adjacent electrodes, in cm; R is the impedance, in Ω; S is the cross-sectional area, in cm 2 .
[0050] Swelling rate: Cut the film sample into a sample with a side length of 2×2cm, soak it in constant temperature deionized water at a specified temperature for 5 hours, take it out, wipe off the surface moisture and record the side length of the wet film. Then dry the sample thoroughly in a vacuum oven and record the side length of the dry film. By changing the temperature of the deionized water, the swelling value under different temperature conditions can be calculated. The formula is:
[0051]
[0052] Where, SR is the swelling ratio; l 湿 is the side length of the sample in wet film condition, in cm; l 干 It is the side length of the sample when it is completely dried, in cm.
[0053] The sources of some substances of the present invention are as follows:
[0054] Polyarylene ether sulfone: Manufacturer: Merck Chemical Technology Co., Ltd., brand: 440965.
[0055] Polysulfone: Manufacturer: Shanghai MacLean Biochemical Technology Co., Ltd., brand: P856835.
[0056] Poly(styrene-b-(ethylene-co-butylene)-b-styrene): Manufacturer: Shanghai MacLean Biochemical Technology Co., Ltd., brand: P922032.
[0057] Poly[2,2'-(m-phenyl)-5,5'-bibenzimidazole]: Manufacturer: Shanghai Shengjun Plastic Technology Co., Ltd., brand: PBISJ-60.
[0058] Poly (2,5-benzimidazole): Manufacturer: Fumatech Technology Co., Ltd., molecular weight 100,000.
[0059] Poly(4,4′-diphenyl ether-5,5′-bibenzimidazole): Manufacturer: Shanghai Shengjun Plastic Technology Co., Ltd., brand: PBISJ-10.
[0060] Polyethylene: Manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., brand: P434351.
[0061] Polynorbornene: Manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., brand: P301648.
[0062] Polystyrene: Manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., brand: P434446.
[0063] Polytetrafluoroethylene: Manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., brand: P434335.
[0064] Paraformaldehyde: Manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., brand: C104188.
[0065] Example 1
[0066] A method for preparing a composite alkaline ion membrane, the specific steps are as follows:
[0067] (1) Preparation of raw materials:
[0068] Polymer A: poly(styrene-b-(ethylene-co-butylene)-b-styrene) (SEBS);
[0069] Catalyst B: anhydrous tin tetrachloride;
[0070] Modification reagent C: 1,4-dichloromethoxybutane (BCMB);
[0071] Solvent D: chloroform;
[0072] Solvent E: ethanol;
[0073] Solvent F: a mixture of chloroform and p-xylene, with the mass ratio of chloroform to p-xylene being 2:1;
[0074] Solvent G: N,N-dimethylacetamide;
[0075] Ionic solvating polymer: poly[2,2'-(m-phenyl)-5,5'-bibenzimidazole] (mPBI);
[0076] (2) Mixing polymer A, catalyst B, and modification agent C in solvent D in an ice water bath, reacting at room temperature for 3 h, and after the reaction is completed, precipitating the product in solvent E, and drying at 30° C. for 24 h to obtain an anion exchange membrane polymer;
[0077] The ratio of the amount of polymer A, catalyst B, modification reagent C, solvent D and solvent E is 2 g: 2.4 mL: 9.2 mL: 60 mL: 350 mL;
[0078] (3) dissolving the anion exchange membrane type polymer obtained in step (2) in solvent F, stirring at room temperature for 20 h until it is completely dissolved to prepare an anion exchange membrane type polymer solution with a concentration of 11 wt %;
[0079] (4) dissolving the ionic solvated polymer in solvent G to prepare a spinning solution, heating and stirring until completely dissolved, then electrospinning, and then drying to obtain an ionic solvated polymer nanofiber membrane;
[0080] The concentration of ion solvated polymer in the spinning solution was 15wt%; the electrospinning process parameters were: temperature 25°C, humidity 25%, voltage 24kV, push speed 0.5mL / h, receiving distance 12cm; drying temperature was 80°C, and drying time was 6h;
[0081] The thickness of the prepared ion-solvated polymer nanofiber membrane is 30 μm, the pore size is 1 to 3 μm, and the porosity is 84%; the diameter of the ion-solvated polymer nanofiber is 500 to 1500 nm;
[0082] (5) coating the anion exchange membrane type polymer solution obtained in step (3) on the surface of the ion solvated polymer nanofiber membrane prepared in step (4) and filling the pores on the membrane, with a coating thickness of 40 μm;
[0083] like Figure 1 As shown, the thickness and pore size distribution of the ion-solvated polymer nanofiber membrane are uniform and have no obvious defects, and the pores therein are completely filled with the anion exchange membrane-type polymer.
[0084] (6) subjecting the ion-solvated polymer nanofiber membrane coated with the anion exchange membrane type polymer solution in step (5) to a cross-linking reaction at 80° C. for 12 hours to obtain a cross-linked membrane;
[0085] (7) immersing the cross-linked membrane obtained in step (6) in a 30 wt % trimethylamine aqueous solution for quaternization reaction for 48 h to obtain a composite membrane;
[0086] The mass fraction of the quaternized anion exchange membrane polymer in the composite membrane is 83wt%;
[0087] (8) The composite membrane obtained in step (7) is immersed in a 1 M potassium hydroxide solution for 24 hours to perform anion exchange reaction to obtain a composite alkaline ion membrane.
[0088] The final composite alkaline ion membrane is a composite membrane composed of a quaternized anion exchange membrane polymer and an ion solvated polymer nanofiber membrane, obtained by anion exchange; Figures 2-3As shown, the quaternized anion exchange membrane-type polymer is distributed on the surface and pores of the ion-solvated polymer nanofiber membrane, and the two are bonded by covalent bonds; the thickness of the composite alkaline ion membrane is 40 μm, the tensile strength of the composite alkaline ion membrane is 36 MPa, and the ion conductivity at 80° C. is 120 mS / cm; the swelling rate of the composite alkaline ion membrane is 12% at 80° C.; the composite alkaline ion membrane is used as an alkaline ion membrane in alkaline water electrolysis to produce hydrogen, alkaline fuel cells, carbon dioxide conversion or electrochemical synthesis of ammonia.
[0089] Comparative Example 1
[0090] A method for preparing an alkaline ion membrane is basically the same as that of Example 1, except that the operation of step (4) is omitted and the anion exchange membrane type polymer solution obtained in step (3) is directly coated on a glass plate.
[0091] The finally prepared alkaline ion membrane had a tensile strength of 30.3 MPa, an ionic conductivity of 75.2 mS / cm at 80° C., and a swelling ratio of 105.3% at 80° C.
[0092] By comparing Comparative Example 1 with Example 1, it can be found that the tensile strength and ionic conductivity of the composite alkaline ion membrane in Example 1 are higher than those of the alkaline ion membrane in Comparative Example 1, and the swelling rate of the composite alkaline ion membrane in Example 1 is significantly lower than that in Comparative Example 1. This is because the introduction of the fiber structure in the composite alkaline ion membrane and the presence of cross-linking improve the mechanical strength, the optimized ion synergistic conduction in the composite alkaline membrane improves the ionic conductivity, and the fiber structure can effectively inhibit swelling and thus improve dimensional stability.
[0093] Comparative Example 2
[0094] A method for preparing an alkaline ion membrane is basically the same as that of Example 1, except that: steps (2), (3), (5), (6), and (7) are omitted, and step (4) is performed directly, and the ion-solvated polymer nanofiber membrane obtained in step (4) is immersed in a 1M potassium hydroxide solution for 24 hours to perform anion exchange reaction to obtain an alkaline ion membrane.
[0095] The tensile strength of the alkaline ion membrane finally prepared is 21.5 MPa, and the ion conductivity at 80°C is 15.8 mS / cm.
[0096] By comparing Comparative Example 2 with Example 1, it can be found that the tensile strength and ion conductivity of the composite alkaline ion membrane in Example 1 are higher than those in Comparative Example 2. This is because the alkaline ion membrane of Comparative Example 2 is porous and loose, with low mechanical strength, and insufficient absorption of alkali and water at low alkali concentration leads to insufficient ion conductivity, while the pores in the composite alkaline ion membrane of Example 1 are filled and cross-linked, which improves the mechanical strength, and the optimized ion transport pathway improves the ion conductivity.
[0097] Example 2
[0098] A method for preparing a composite alkaline ion membrane, the specific steps are as follows:
[0099] (1) Preparation of raw materials:
[0100] Polymer A: polyarylene ether sulfone (PAES);
[0101] Catalyst B: aluminum chloride;
[0102] Modification reagent C: chloromethyl ether;
[0103] Solvent D: chloroform;
[0104] Solvent E: ethanol;
[0105] Solvent F: a mixture of chloroform and p-xylene, with the mass ratio of chloroform to p-xylene being 2:1;
[0106] Solvent G: N,N-dimethylacetamide;
[0107] Ionic solvating polymer: poly(4,4′-diphenyl ether-5,5′-bibenzimidazole) (OPBI);
[0108] (2) Mixing polymer A, catalyst B, and modification agent C in solvent D in an ice water bath, reacting at room temperature for 5 hours, and after the reaction is completed, precipitating the product in solvent E, and drying at 80° C. for 24 hours to obtain an anion exchange membrane polymer;
[0109] The ratio of the amount of polymer A, catalyst B, modification reagent C, solvent D and solvent E is 2 g: 2.4 mL: 20 mL: 60 mL: 350 mL;
[0110] (3) dissolving the anion exchange membrane type polymer obtained in step (2) in solvent F, stirring at room temperature for 30 hours to completely dissolve the anion exchange membrane type polymer solution with a concentration of 8 wt %;
[0111] (4) dissolving the ionic solvated polymer in solvent G to prepare a spinning solution, heating and stirring until completely dissolved, then electrospinning, and then drying to obtain an ionic solvated polymer nanofiber membrane;
[0112] The concentration of ion solvated polymer in the spinning solution was 10 wt %; the electrospinning process parameters were: temperature 35°C, humidity 35%, voltage 18 kV, push speed 0.1 mL / h, receiving distance 16 cm; drying temperature 60°C, drying time 18 h;
[0113] The thickness of the prepared ion-solvated polymer nanofiber membrane is 34 μm, the pore size is 0.8-1.5 μm, and the porosity is 90%; the diameter of the ion-solvated polymer nanofiber is 400-800 nm;
[0114] (5) coating the anion exchange membrane type polymer solution obtained in step (3) on the surface of the ion solvated polymer nanofiber membrane prepared in step (4) and filling the pores on the membrane, with a coating thickness of 40 μm;
[0115] (6) subjecting the ion-solvated polymer nanofiber membrane coated with the anion exchange membrane type polymer solution in step (5) to a cross-linking reaction at 60° C. for 18 hours to obtain a cross-linked membrane;
[0116] (7) immersing the cross-linked membrane obtained in step (6) in a 30 wt % trimethylamine aqueous solution for quaternization reaction for 48 h to obtain a composite membrane;
[0117] Wherein, the mass fraction of the quaternized anion exchange membrane polymer in the composite membrane is 90wt%;
[0118] (8) The composite membrane obtained in step (7) was immersed in a 3M potassium hydroxide solution for 48 hours to perform anion exchange reaction to obtain a composite alkaline ion membrane.
[0119] The composite alkaline ion membrane finally prepared is a composite membrane composed of a quaternized anion exchange membrane type polymer and an ion solvation polymer nanofiber membrane obtained by anion exchange; the quaternized anion exchange membrane type polymer is distributed on the surface and pores of the ion solvation polymer nanofiber membrane, and the two are combined by covalent bonds; the thickness of the composite alkaline ion membrane is 42 μm, the tensile strength of the composite alkaline ion membrane is 20 MPa, and the ion conductivity at 80°C is 94 mS / cm; the swelling rate of the composite alkaline ion membrane at 80°C is 13.5%; the composite alkaline ion membrane is used as an alkaline ion membrane in alkaline water electrolysis to produce hydrogen, alkaline fuel cells, carbon dioxide conversion or electrochemical synthesis of ammonia.
[0120] Comparative Example 3
[0121] A method for preparing an alkaline ion membrane is basically the same as that of Example 2, except that the operation of step (4) is omitted and the anion exchange membrane type polymer solution obtained in step (3) is directly coated on a glass plate.
[0122] The finally prepared alkaline ion membrane had a tensile strength of 16.7 MPa, an ionic conductivity of 49.6 mS / cm at 80° C., and a swelling ratio of 18.8% at 80° C.
[0123] By comparing Comparative Example 3 with Example 2, it can be found that the tensile strength and ionic conductivity of the composite alkaline ion membrane in Example 2 are higher than those of the alkaline ion membrane in Comparative Example 3, while the swelling rate in Example 2 is significantly lower than that in Comparative Example 3. This is because compared with Comparative Example 3, the introduction of the fiber structure in the composite alkaline ion membrane in Example 2 and the presence of cross-linking improve the mechanical strength, the optimized ion synergistic conduction in the composite alkaline ion membrane improves the ionic conductivity, and the fiber structure in the composite alkaline ion membrane effectively inhibits swelling.
[0124] Example 3
[0125] A method for preparing a composite alkaline ion membrane, the specific steps are as follows:
[0126] (1) Preparation of raw materials:
[0127] Polymer A: polysulfone (PSU);
[0128] Catalyst B: zinc chloride;
[0129] Modification reagent C: paraformaldehyde and 6-bromohexanoyl chloride in a mass ratio of 1:1;
[0130] Solvent D: chloroform;
[0131] Solvent E: ethanol;
[0132] Solvent F: a mixture of chloroform and p-xylene, with the mass ratio of chloroform to p-xylene being 2:1;
[0133] Solvent G: N,N-dimethylacetamide;
[0134] Ionic solvating polymer: poly(2,5-benzimidazole) (ABPBI);
[0135] (2) Mixing polymer A, catalyst B, and modification agent C in solvent D in an ice water bath, reacting at room temperature for 7 hours, and after the reaction is completed, precipitating the product in solvent E, and drying at 30° C. for 24 hours to obtain an anion exchange membrane polymer;
[0136] The ratio of the amount of polymer A, catalyst B, modification reagent C, solvent D and solvent E is 2 g: 2.4 mL: 10 mL: 60 mL: 350 mL;
[0137] (3) dissolving the anion exchange membrane type polymer obtained in step (2) in solvent F, stirring at room temperature for 10 h until it is completely dissolved to prepare an anion exchange membrane type polymer solution with a concentration of 9 wt %;
[0138] (4) dissolving the ionic solvated polymer in solvent G to prepare a spinning solution, heating and stirring until completely dissolved, then electrospinning, and then drying to obtain an ionic solvated polymer nanofiber membrane;
[0139] The concentration of ion solvated polymer in the spinning solution is 20wt%; the electrospinning process parameters are: temperature 30°C, humidity 30%, voltage 20kV, push speed 0.2mL / h, receiving distance 12cm; drying temperature 70°C, drying time 12h;
[0140] The thickness of the prepared ion-solvated polymer nanofiber membrane is 36 μm, the pore size is 4-7 μm, and the porosity is 70%; the diameter of the ion-solvated polymer nanofiber is 800-2000 nm;
[0141] (5) coating the anion exchange membrane type polymer solution obtained in step (3) on the surface of the ion solvated polymer nanofiber membrane prepared in step (4) and filling the pores on the membrane, with a coating thickness of 40 μm;
[0142] (6) subjecting the ion-solvated polymer nanofiber membrane coated with the anion exchange membrane type polymer solution in step (5) to a cross-linking reaction at 120° C. for 6 hours to obtain a cross-linked membrane;
[0143] (7) immersing the cross-linked membrane obtained in step (6) in a 30 wt % trimethylamine aqueous solution for quaternization reaction for 48 h to obtain a composite membrane;
[0144] The mass fraction of the quaternized anion exchange membrane polymer in the composite membrane is 60%;
[0145] (8) The composite membrane obtained in step (7) was immersed in a 6M potassium hydroxide solution for 100 hours to perform anion exchange reaction to obtain a composite alkaline ion membrane.
[0146] The composite alkaline ion membrane finally prepared is a composite membrane composed of a quaternized anion exchange membrane type polymer and an ion solvated polymer nanofiber membrane obtained by anion exchange; the quaternized anion exchange membrane type polymer is distributed on the surface and pores of the ion solvated polymer nanofiber membrane, and the two are bonded by covalent bonds; the thickness of the composite alkaline ion membrane is 44 μm, the tensile strength of the composite alkaline ion membrane is 32 MPa, and the ion conductivity at 80°C is 106 mS / cm; the swelling rate of the composite alkaline ion membrane at 80°C is 8%; the composite alkaline ion membrane is used as an alkaline ion membrane in alkaline water electrolysis to produce hydrogen, alkaline fuel cells, carbon dioxide conversion or electrochemical synthesis of ammonia.
[0147] Comparative Example 4
[0148] A method for preparing an alkaline ion membrane is basically the same as that of Example 3, except that the operation of step (4) is omitted and the anion exchange membrane type polymer solution obtained in step (3) is directly coated on a glass plate.
[0149] The finally prepared alkaline ion membrane had a tensile strength of 27.5 MPa, an ionic conductivity of 47.1 mS / cm at 80° C., and a swelling ratio of 22.8% at 80° C.
[0150] By comparing Comparative Example 4 with Example 3, it can be found that the tensile strength and ion conductivity of the composite alkaline ion membrane in Example 3 are higher than those of the alkaline ion membrane prepared by the anion exchange membrane type polymer used, and the swelling rate in Example 3 is significantly reduced. This is because compared with Comparative Example 4, the introduction of the fiber structure in the composite alkaline ion membrane in Example 3 and the presence of cross-linking improve the mechanical strength, the optimized ion synergistic conduction effect in the composite alkaline membrane improves the ion conductivity, and the fiber structure in the composite alkaline ion membrane effectively inhibits swelling and thus improves dimensional stability.
[0151] Example 4
[0152] A method for preparing a composite alkaline ion membrane, the specific steps are as follows:
[0153] (1) Preparation of raw materials:
[0154] Polymer A: polyethylene;
[0155] Catalyst B: zinc chloride and concentrated hydrochloric acid (concentration 37wt%);
[0156] Modification reagent C: paraformaldehyde and 6-bromohexanoyl chloride in a mass ratio of 1:1;
[0157] Solvent D: p-xylene;
[0158] Solvent E: methanol;
[0159] Solvent F: a mixture of chloroform and p-xylene, with the mass ratio of chloroform to p-xylene being 2:1;
[0160] Solvent G: N,N-dimethylformamide;
[0161] Ionic solvating polymer: poly[2,2'-(m-phenyl)-5,5'-bibenzimidazole];
[0162] (2) Mixing polymer A, catalyst B, and modification agent C in solvent D in an ice water bath, reacting at room temperature for 5 hours, and after the reaction is completed, precipitating the product in solvent E, and drying at 60° C. for 32 hours to obtain an anion exchange membrane polymer;
[0163] The ratio of the amount of polymer A, catalyst B, modification reagent C, solvent D and solvent E is 1 g: 1 mL: 5 mL: 40 mL: 200 mL;
[0164] (3) dissolving the anion exchange membrane type polymer obtained in step (2) in solvent F, stirring at room temperature for 10 h until it is completely dissolved to prepare an anion exchange membrane type polymer solution with a concentration of 12 wt %;
[0165] (4) dissolving the ionic solvated polymer in solvent G to prepare a spinning solution, heating and stirring until completely dissolved, then electrospinning, and then drying to obtain an ionic solvated polymer nanofiber membrane;
[0166] The concentration of ion solvated polymer in the spinning solution is 20wt%; the electrospinning process parameters are: temperature 28°C, humidity 25%, voltage 24kV, push speed 0.2mL / h, receiving distance 12cm; drying temperature is 80°C, and drying time is 12h;
[0167] The thickness of the prepared ion-solvated polymer nanofiber membrane is 38 μm, the pore size is 2-5 μm, and the porosity is 76%; the diameter of the ion-solvated polymer nanofiber is 700-1800 nm;
[0168] (5) coating the anion exchange membrane type polymer solution obtained in step (3) on the surface of the ion solvated polymer nanofiber membrane prepared in step (4) and filling the pores on the membrane, with a coating thickness of 40 μm;
[0169] (6) subjecting the ion-solvated polymer nanofiber membrane coated with the anion exchange membrane type polymer solution in step (5) to a cross-linking reaction at 90° C. for 8 h to obtain a cross-linked membrane;
[0170] (7) immersing the cross-linked membrane obtained in step (6) in a 30 wt % trimethylamine aqueous solution for quaternization reaction for 48 h to obtain a composite membrane;
[0171] The mass fraction of the quaternized anion exchange membrane polymer in the composite membrane is 74wt%;
[0172] (8) The composite membrane obtained in step (7) is immersed in a 1M sodium hydroxide solution for 48 hours to perform anion exchange reaction to obtain a composite alkaline ion membrane.
[0173] The composite alkaline ion membrane finally prepared is a composite membrane composed of a quaternized anion exchange membrane type polymer and an ion solvation polymer nanofiber membrane obtained by anion exchange; the quaternized anion exchange membrane type polymer is distributed on the surface and pores of the ion solvation polymer nanofiber membrane, and the two are combined by covalent bonds; the thickness of the composite alkaline ion membrane is 45 μm, the tensile strength of the composite alkaline ion membrane is 28 MPa, and the ion conductivity at 80°C is 50 mS / cm; the swelling rate of the composite alkaline ion membrane at 80°C is 9.2%; the composite alkaline ion membrane is used as an alkaline ion membrane in alkaline water electrolysis to produce hydrogen, alkaline fuel cells, carbon dioxide conversion or electrochemical synthesis of ammonia.
[0174] Example 5
[0175] A method for preparing a composite alkaline ion membrane, the specific steps are as follows:
[0176] (1) Preparation of raw materials:
[0177] Polymer A: polystyrene and polynorbornene in a mass ratio of 1:1;
[0178] Catalyst B: anhydrous tin tetrachloride and aluminum trichloride in a mass ratio of 1:1;
[0179] Modification reagent C: 1,4-dichloromethoxybutane and chloromethyl ether in a mass ratio of 1:1;
[0180] Solvent D: chloroform and p-xylene in a mass ratio of 1:1;
[0181] Solvent E: methanol and ethanol in a volume ratio of 1:1;
[0182] Solvent F: a mixture of chloroform and p-xylene, with the mass ratio of chloroform to p-xylene being 2:1;
[0183] Solvent G: dimethyl sulfoxide;
[0184] Ionic solvating polymer: poly(2,5-benzimidazole);
[0185] (2) Mixing polymer A, catalyst B, and modification agent C in solvent D in an ice water bath, reacting at room temperature for 6 hours, and after the reaction is completed, precipitating the product in solvent E, and drying at 80° C. for 24 hours to obtain an anion exchange membrane polymer;
[0186] The ratio of the amount of polymer A, catalyst B, modification reagent C, solvent D and solvent E is 2 g: 1.4 mL: 9.2 mL: 60 mL: 400 mL;
[0187] (3) dissolving the anion exchange membrane type polymer obtained in step (2) in solvent F, stirring at room temperature for 20 h until it is completely dissolved to prepare an anion exchange membrane type polymer solution with a concentration of 10 wt%;
[0188] (4) dissolving the ionic solvated polymer in solvent G to prepare a spinning solution, heating and stirring until completely dissolved, then electrospinning, and then drying to obtain an ionic solvated polymer nanofiber membrane;
[0189] The concentration of ion solvated polymer in the spinning solution was 20 wt %; the electrospinning process parameters were: temperature 28°C, humidity 25%, voltage 24 kV, push speed 0.2 mL / h, receiving distance 16 cm; drying temperature 80°C, drying time 12 h;
[0190] The thickness of the prepared ion-solvated polymer nanofiber membrane is 40 μm, the pore size is 2-6 μm, and the porosity is 74%; the diameter of the ion-solvated polymer nanofiber is 600-1700 nm;
[0191] (5) coating the anion exchange membrane type polymer solution obtained in step (3) on the surface of the ion solvated polymer nanofiber membrane prepared in step (4) and filling the pores on the membrane, with a coating thickness of 40 μm;
[0192] (6) subjecting the ion-solvated polymer nanofiber membrane coated with the anion exchange membrane type polymer solution in step (5) to a cross-linking reaction at 120° C. for 12 hours to obtain a cross-linked membrane;
[0193] (7) immersing the cross-linked membrane obtained in step (6) in a 30 wt % trimethylamine aqueous solution for quaternization reaction for 48 h to obtain a composite membrane;
[0194] The mass fraction of the quaternized anion exchange membrane polymer in the composite membrane is 79wt%;
[0195] (8) The composite membrane obtained in step (7) was immersed in a 3M sodium hydroxide solution for 72 hours to perform anion exchange reaction to obtain a composite alkaline ion membrane.
[0196] The composite alkaline ion membrane finally prepared is a composite membrane composed of a quaternized anion exchange membrane type polymer and an ion solvation polymer nanofiber membrane obtained by anion exchange; the quaternized anion exchange membrane type polymer is distributed on the surface and pores of the ion solvation polymer nanofiber membrane, and the two are combined by covalent bonds; the thickness of the composite alkaline ion membrane is 48 μm, the tensile strength of the composite alkaline ion membrane is 50 MPa, and the ion conductivity at 80°C is 76 mS / cm; the swelling rate of the composite alkaline ion membrane at 80°C is 10.6%; the composite alkaline ion membrane is used as an alkaline ion membrane in alkaline water electrolysis to produce hydrogen, alkaline fuel cells, carbon dioxide conversion or electrochemical synthesis of ammonia.
[0197] Example 6
[0198] A method for preparing a composite alkaline ion membrane, the specific steps are as follows:
[0199] (1) Preparation of raw materials:
[0200] Polymer A: polytetrafluoroethylene and poly(styrene-b-(ethylene-co-butylene)-b-styrene) in a mass ratio of 1:1;
[0201] Catalyst B: aluminum chloride and zinc chloride in a mass ratio of 1:1;
[0202] Modification reagent C: chloromethyl ether, paraformaldehyde and 6-bromohexanoyl chloride in a mass ratio of 2:1:1;
[0203] Solvent D: chloroform and p-xylene in a mass ratio of 1:1;
[0204] Solvent E: ethanol and propanol in a volume ratio of 1:1;
[0205] Solvent F: a mixture of chloroform and p-xylene, with the mass ratio of chloroform to p-xylene being 2:1;
[0206] Solvent G: N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 1:1;
[0207] Ionic solvation polymer: poly(2,5-benzimidazole) (ABPBI) and poly(4,4′-diphenyl ether-5,5′-bibenzimidazole) in a mass ratio of 1:1;
[0208] (2) Mixing polymer A, catalyst B, and modification agent C in solvent D in an ice water bath, reacting at room temperature for 7 hours, and after the reaction is completed, precipitating the product in solvent E, and drying at 30° C. for 48 hours to obtain an anion exchange membrane polymer;
[0209] The ratio of the amount of polymer A, catalyst B, modification reagent C, solvent D and solvent E is 5 g: 4 mL: 20 mL: 80 mL: 500 mL;
[0210] (3) dissolving the anion exchange membrane type polymer obtained in step (2) in solvent F, stirring at room temperature for 30 hours to completely dissolve the anion exchange membrane type polymer solution with a concentration of 10 wt%;
[0211] (4) dissolving the ionic solvated polymer in solvent G to prepare a spinning solution, heating and stirring until completely dissolved, then electrospinning, and then drying to obtain an ionic solvated polymer nanofiber membrane;
[0212] The concentration of ion solvated polymer in the spinning solution was 10 wt %; the electrospinning process parameters were: temperature 28°C, humidity 25%, voltage 24 kV, push speed 0.2 mL / h, receiving distance 12 cm; drying temperature 80°C, drying time 12 h;
[0213] The thickness of the prepared ion-solvated polymer nanofiber membrane is 40 μm, the pore size is 1-2 μm, and the porosity is 86%; the diameter of the ion-solvated polymer nanofiber is 400-1000 nm;
[0214] (5) coating the anion exchange membrane type polymer solution obtained in step (3) on the surface of the ion solvated polymer nanofiber membrane prepared in step (4) and filling the pores on the membrane, with a coating thickness of 40 μm;
[0215] (6) subjecting the ion-solvated polymer nanofiber membrane coated with the anion exchange membrane type polymer solution in step (5) to a cross-linking reaction at 60° C. for 16 hours to obtain a cross-linked membrane;
[0216] (7) immersing the cross-linked membrane obtained in step (6) in a 30 wt % trimethylamine aqueous solution for quaternization reaction for 48 h to obtain a composite membrane;
[0217] The mass fraction of the quaternized anion exchange membrane polymer in the composite membrane is 89wt%;
[0218] (8) The composite membrane obtained in step (7) was immersed in a 6M potassium hydroxide solution for 24 hours to perform anion exchange reaction to obtain a composite alkaline ion membrane.
[0219] The composite alkaline ion membrane finally prepared is a composite membrane composed of a quaternized anion exchange membrane type polymer and an ion solvation polymer nanofiber membrane obtained by anion exchange; the quaternized anion exchange membrane type polymer is distributed on the surface and pores of the ion solvation polymer nanofiber membrane, and the two are combined by covalent bonds; the thickness of the composite alkaline ion membrane is 50 μm, the tensile strength of the composite alkaline ion membrane is 24 MPa, and the ion conductivity at 80°C is 55 mS / cm; the swelling rate of the composite alkaline ion membrane at 80°C is 14%; the composite alkaline ion membrane is used as an alkaline ion membrane in alkaline water electrolysis to produce hydrogen, alkaline fuel cells, carbon dioxide conversion or electrochemical synthesis of ammonia.
Claims
1. A composite alkaline ion membrane, characterized in that: The composite membrane composed of quaternized anion exchange membrane polymer and ion solvated polymer nanofiber membrane is obtained by anion exchange; The quaternized anion exchange membrane polymer is distributed on the surface and in the pores of the ion solvated polymer nanofiber membrane, and the two are bound by covalent bonds.
2. A composite alkaline ion membrane according to claim 1, characterized in that: The anion exchange membrane type polymer is prepared by halogen modification of polymer A, wherein polymer A is one or more of polyphenylene ether, polyarylene ether sulfone, polyarylene ether ketone, polyethylene, polystyrene, polynorbornene, polytetrafluoroethylene, poly(styrene-b-(ethylene-co-butylene)-b-styrene) and polysulfone, and the halogen modification method is one or more of chloromethylation and bromohexylation.
3. A composite alkaline ion membrane according to claim 1, characterized in that: The ionic solvated polymer nanofiber membrane is prepared by electrostatic spinning of an ionic solvated polymer, wherein the ionic solvated polymer is one or more of poly[2,2'-(m-phenyl)-5,5'-bibenzimidazole], poly(2,5-benzimidazole) and poly(4,4'-diphenyl ether-5,5'-bibenzimidazole).
4. A composite alkaline ion membrane according to claim 1, characterized in that: The mass fraction of the quaternized anion exchange membrane polymer in the composite membrane is 60-90%.
5. A composite alkaline ion membrane according to claim 1, characterized in that: The thickness of the composite alkaline ion membrane is 40-50 μm, the tensile strength of the composite alkaline ion membrane is 20-50 MPa, the swelling rate at 80° C. is 8-14%, and the ion conductivity at 80° C. is 50-120 mS / cm.
6. A composite alkaline ion membrane according to claim 1, characterized in that: The thickness of the ion-solvated polymer nanofiber membrane is 30-40 μm, the pore size is 0.8-7 μm, and the porosity is 70-90%; the diameter of the ion-solvated polymer nanofiber is 400-2000 nm.
7. A method for preparing a composite alkaline ion membrane according to any one of claims 1 to 6, characterized in that: The anion exchange membrane type polymer solution is coated on the surface of the ion solvated polymer nanofiber membrane and filled into the pores on the membrane, and then a cross-linking reaction, a quaternization reaction and anion exchange reaction are sequentially performed to obtain a composite alkaline ion membrane.
8. The method for preparing a composite alkaline ion membrane according to claim 7, characterized in that: The specific preparation steps are as follows: (1) Mixing polymer A, catalyst B, and modifying agent C in solvent D in an ice water bath, reacting at room temperature, and after the reaction is completed, precipitating the product in solvent E, and drying to obtain an anion exchange membrane polymer; (2) dissolving the anion exchange membrane type polymer obtained in step (1) in solvent F, and stirring at room temperature to completely dissolve the anion exchange membrane type polymer solution; (3) dissolving the ionic solvated polymer in solvent G to prepare a spinning solution, heating and stirring until completely dissolved, then electrospinning, and then drying to obtain an ionic solvated polymer nanofiber membrane; (4) coating the anion exchange membrane type polymer solution obtained in step (2) on the surface of the ion solvated polymer nanofiber membrane prepared in step (3) and filling the pores on the membrane; (5) subjecting the ion-solvated polymer nanofiber membrane coated with the anion exchange membrane type polymer solution in step (4) to a cross-linking reaction to obtain a cross-linked membrane; (6) soaking the cross-linked membrane obtained in step (5) in a trimethylamine solution for quaternization reaction to obtain a composite membrane; (7) Immersing the composite membrane obtained in step (6) in a sodium hydroxide solution or a potassium hydroxide solution to carry out anion exchange reaction, thereby obtaining a composite alkaline ion membrane.
9. The method for preparing a composite alkaline ion membrane according to claim 7, characterized in that: In step (1), the catalyst B is one or more of anhydrous tin tetrachloride, aluminum chloride, zinc chloride and concentrated hydrochloric acid, the modification reagent C is one or more of 1,4-dichloromethoxybutane, chloromethyl ether, paraformaldehyde and 6-bromohexanoyl chloride, the solvent D is one or more of chloroform and p-xylene, and the solvent E is one or more of methanol, ethanol and propanol; the ratio of the amount of polymer A, catalyst B, modification reagent C, solvent D and solvent E is 1-5g:1-4mL:5-20mL:40-80mL:200-500mL; the reaction time at room temperature is 3-7h, the drying temperature is 30-80°C, and the drying time is 24-48h; In step (2), the solvent F is a mixture of chloroform and p-xylene, the mass ratio of chloroform to p-xylene is 2:1; the concentration of the anion exchange membrane polymer solution is 8 to 12 wt %; the time of stirring and dissolving at room temperature is 10 to 30 h; In step (3), the solvent G is one or more of N,N-dimethylacetamide, N,N-dimethylformamide and dimethyl sulfoxide; the concentration of the ionic solvated polymer in the spinning solution is 10-20wt%; the electrospinning process parameters are: temperature 25-35°C, humidity 25-35%, voltage 18-24kV, push speed 0.1-0.5mL / h, receiving distance 12-16cm; drying temperature is 60-80°C, and drying time is 6-18h; In step (5), the cross-linking reaction temperature is 60 to 120° C. and the time is 6 to 18 hours; In step (6), the concentration of the trimethylamine solution is 30wt%, and the quaternization reaction time is 48h; In step (7), the concentration of the sodium hydroxide solution or the potassium hydroxide solution is 1 to 6 M, and the soaking time is 24 to 100 hours.
10. The use of a composite alkaline ion membrane according to any one of claims 1 to 6, characterized in that: Used as alkaline ion membrane in alkaline water electrolysis to produce hydrogen, alkaline fuel cells, carbon dioxide conversion or electrochemical synthesis of ammonia.
Citation Information
Patent Citations
Fiber-reinforced side chain grafted OH<-> type anion exchange membrane as well as preparation and application thereof
CN113249980A
Preparation method of cross-linking type composite anion-exchange membrane
CN103387690A
PBI fiber membrane reinforced high-temperature-resistant composite proton exchange membrane and preparation method thereof
CN110739476A
Ultrathin cross-linked composite enhanced polymer anion exchange membrane and preparation method and application thereof
CN111244512A
Self-supporting nanofiber anion exchange chromatography membrane and preparation method thereof
CN114177787A
Cited By
Polynorbornene-based composite anion exchange membrane as well as preparation method and application thereof
CN121574485A
Novel composite bipolar membrane for preparing low-carbon alcohol alkali metal salt and electrodialysis process thereof
CN121695718A